Asian American Pacific Heritage Week April 27, 29, and 30, 1981 - Asian Student Union, Hayward::::::; Associated Students:::::: (1981)
A program of events for Asian American Pacific Heritage Week held April 27, 29, and 30, 1981, at Cal State Hayward. "During the week of April 27-30, 1981, the members of the Asian Student Union will present speakers and events which will share some of the history and culture of Asian Americans. We hope to provide participants with an increased awareness and deeper understanding of the heritage and culture which has played an integral part in shaping our lives."